Detection of prostate cancer in unselected young men: prospective cohort nested within a randomised controlled trial. - Lane, J; Howson, J; Donovan, J; Goepel, JR; Dedman, D; Down, L; Turner, E; Neal, D; Hamdy, F (2007)
OBJECTIVE: To investigate the feasibility of testing for prostate cancer and the prevalence and characteristics of the disease in unselected young men. DESIGN: Prospective cohort nested within a randomised controlled trial, with two years of follow-up. SETTING: Eight general practices in a UK city. PARTICIPANTS: 1299 unselected men aged 45-49. INTERVENTION: Prostate biopsies for participants with a prostate specific antigen level of 1.5 ng/ml or more and the possibility of randomisation to three treatments for those with localised prostate cancer. MAIN OUTCOME MEASURES: Uptake of testing for prostate specific antigen; positive predictive value of prostate specific antigen; and prevalence of prostate cancer, TNM disease stage, and histological grade (Gleason score). RESULTS: 442 of 1299 men agreed to be tested for prostate specific antigen (34%) and 54 (12%) had a raised level. The positive predictive value for prostate specific antigen was 21.3%. Ten cases of prostate cancer were detected (2.3%) with eight having at least two positive results in biopsy cores and three showing perineural invasion. One tumour was of high volume (cT2c), Gleason score 7, with a positive result on digital rectal examination; nine tumours were cT1c, Gleason score 6, and eight had a negative result on digital rectal examination. Five of the nine eligible participants (55%) agreed to be randomised. No biochemical disease progression in the form of a rising prostate specific antigen level occurred in two years of follow-up. CONCLUSIONS: Men younger than 50 will accept testing for prostate cancer but at a much lower rate than older men. Using an age based threshold of 1.5 ng/ml, the prevalence of prostate cancer was similar to that in older men (3.0 ng/ml threshold) and some cancers of potential clinical significance were found. TRIAL REGISTRATION: Current Controlled Trials ISRCTN20141297.